The Influence of Liquidity, Profitability, and Leverage on Financial Distress Prediction in Manufacturing Companies of The Food and Beverage Sub-Sector Listed in The Indonesia Stock Exchange (IDX) - Anggrainy, Devy; Maslichah, Maslichah; Sudaryanti, Dwiyani (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The aim of this study is to examine how liquidity, profitability, and leverage influence the potential of financial distress in manufacturing companies in the food and beverage subsector that have been listed on the Indonesia Stock Exchange (IDX) for the period 2020 to 2022. There are four variables used, namely liquidity with cash ratio (CR) measurement indicators, profitability using return on capital employed (ROCE), leverage with long term debt to equity ratio (LDR), and financial distress measured by interest coverage ratio (ICR). The sampling technique used was purposive sampling and resulted in a sample of 38 companies and 84 financial reports. Data has been collected through documentation, and multiple linear regression analysis was employed for analysis. The results showed that: 1) Liquidity has a negative effect on financial distress 2) Profitability has a negative effect on financial distress, while 3) Leverage has no effect on financial distress. Keywords: Liquidity, profitability, leverage, financial distress, cash ratio (CR), return on capital employed (ROCE), long term debt to equity ratio (LDR), interest coverage ratio (ICR).